Comparative Analysis of Arabic Textbook Tsanawi Grade 6 Mathayom with Al-Ashri Class 12 in Perspectives of the National Education Standards Agency in Aspects: Feasibility of Content, Language, Presentation and Graphic: Analisis Perbandingan Buku Teks Bahasa Arab Tsanawi Kelas 6 Mathayom Dengan Al - Ashri Kelas 12 Dalam Perspektif Badan Standar Nasional Pendidikan Dalam Aspek: Kelayakan Isi, Bahasa, Penyajian dan Kegrafikan - Risang Mahatmono; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2020)
Textbooks are the basic foundation at all levels of education which play an important role in the learning process. Which contains learning material with good content standards. This study aims to determine and compare the quality of Arabic textbooks